Pronghorn Dental Age Profiles and Holocene Hunting Strategies at Hogup Cave, Utah. Issue 2 (20th April 2009) - Byers, David A.; Hill, Brenda L.
Abstract : In this article, we use pronghorn dental age data to document pronghorn hunting strategies at Hogup Cave, Utah, and explore their relationship with a widespread late Holocene trend in increasing large-game abundances noted in archaeofaunal contexts throughout western North America. Specifically, we test the hypothesis that at Hogup Cave, pronghorn hunting methods changed from a middle Holocene strategy dominated by encounter hunting of individual animals to a late Holocene strategy emphasizing large-scale communal hunting. Our analysis suggests that ancient hunters visiting Hogup Cave most likely employed small-scale encounter hunting during the fall and winter months and that this subsistence pattern varied little between the middle and late Holocene. Moreover, while hunting strategies appear to have remained generally similar throughout the 8, 800-year occupational record at Hogup Cave, artiodactyl abundances show a dramatic increase relative to smaller, lower-ranked prey in late Holocene strata, suggesting that a temporal shift in the favored hunting strategy, by itself, cannot explain this trend in every context.